Nowa przestrzeń biblioteczna, nowe rozwiązania, nowe zadania – proces zmian i rozwoju bibliotek naukowych na przykładzie Biblioteki wydziału Fizyki, astronomii i informatyki stosowanej Uniwersytetu Jagiellońskiego - Wichman, J. (My University, 2015)
Przeprowadzka Instytutu Fizyki UJ ze starego budynku przy ulicy Reymonta 4 do nowych pomieszczeń na III Kampusie UJ dała możliwość stworzenia nowoczesnej, funkcjonalnej, spełniającej standardy europejskie biblioteki naukowej. Biblioteka w nowej, zmienionej formie, będącej wynikiem współpracy bibliotekarzy i architektów oferuje czytelnikom wolny dostęp do książek, stanowiska komputerowe, wygodne czytelnie, aneks wystawowy. Wprowadzony nowoczesny system technologii radiowej RFID (Radio Frequency Identification) połączony z komputerowym systemem bibliotecznym, identyfikuje czytelnika i książki. Nowoczesne urządzenia biblioteczne umożliwiają samodzielne wypożyczanie i zwrot książek. Biblioteka prowadzi działalność naukowo-bibliograficzną, edukacyjną, organizowane są wystawy. Rozpoczęto digitalizację

The big move of the Jagiellonian University Faculty of Physics from the old building at 4 Reymonta Street to the new premises of the 3rd Jagiellonian University Campus at 11 Prof. Stanisław Łojasiewicz Street provided a perfect opportunity for creating a practical, modern and up-to-all-European-standards academic library. Being the result of a close cooperation between the architects and the librarians, the Library in this new form offers a free access to books, computer consoles, comfortable reading rooms and an exhibition hall. Having been linked with a library computer system, a new radio-technology-based system called RFID (Radio Frequency Identification) enables the identification of both library users and books. Modern technology based library devices allow the borrow – return procedures to be carried out by library users themselves. The Library runs a variety of activities including compiling reference materials, organising educational meetings and exhibitions. The digitalisation of selected 19th century works has just started, merging them with the contents of the Digital Jagiellonian Library.

Переїзд Інституту фізики Ягеллонського університету зі старого будинку на вул. Реймонта до нових приміщень третього кампусу сприяв створенню сучасної багатофункціональної наукової бібліотеки згідно європейських стандартів. Нова модернізована бібліотека, що постала у результаті тісної співпраці бібліотекарів і архітекторів пропонує читачам вільний доступ до книжок, користувачам автоматизовані робочі місця, комфортні читальні зали, виставкові площі. Впровадження технології RFID в інтеграції з автоматизованою бібліотечною системою дає змогу ідентифікувати читачів і книжки. Сучасні автоматизовані бібліотечні пристрої уможливлюють самостійно здійснювати запис і реєстрацію документів на абонемент і повернення літератури. Бібліотека виконує науково-бібліографічну, інформаційно-освітню, виставкову діяльність. Розпочато поповнення Ягеллонської цифрової бібліотеки шляхом дигіталізації частини фонду видань ХІХ ст.
Spacious premises, modern technological solutions and new challenges. the library of the Jagiellonian University faculty of physics, astronomy and applied computer science as an example of a changing process and the development of Contemporary academic libraries
Новий бібліотечний простір, нові рішення, нові завдання - процес змін і розвитку наукових бібліотек на прикладі бібліотеки факультету Фізики, астрономії та прикладної інформатики Ягеллонського університету
Keywords: Ягеллонский университет (Краков); Ягеллонський університет (Краків); бібліотека вищого навчального закладу; библиотека высшего учебного заведения; научная библиотека; наукова бібліотека; biblioteki (budynki); biblioteki naukowe; biblioteki naukowe – zagospodarowanie przestrzeni; biblioteki akademickie; biblioteki akademickie – wykorzystanie; library buildings; research libraries; research libraries – space utilization; academic libraries; academic libraries – use studies